2013
DOI: 10.2190/cs.15.2.f
|View full text |Cite
|
Sign up to set email alerts
|

University 100 Orientation Courses and Living-Learning Communities Boost Academic Retention and Graduation via Enhanced Self-Efficacy and Self-Regulated Learning

Abstract: Nationwide, almost a third of 1st-year college students do not return to begin their sophomore year, and the 5-year graduation rate for undergraduates is only around 40%. It is important for universities to implement interventions, such as freshman transition courses, to help new students adjust to college life and succeed, and it is critical that such programs are evaluated to see if they are reaching their goals. The present study examined short-term self-efficacy and self-regulated learning, and long-term a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 19 publications
3
46
0
1
Order By: Relevance
“…Students also use these settings to talk about transition concerns and ways to manage academics as well as social aspects of the undergraduate student experience. These living-learning programs are often supported by institutional staff and faculty members who serve as mentors (Cambridge-Williams, Winsler, Kitsantas, & Bernard, 2013). In addition, students are expected to benefit from peer mentoring in these communities, as discussed later in this chapter.…”
Section: Program Form and Structurementioning
confidence: 99%
“…Students also use these settings to talk about transition concerns and ways to manage academics as well as social aspects of the undergraduate student experience. These living-learning programs are often supported by institutional staff and faculty members who serve as mentors (Cambridge-Williams, Winsler, Kitsantas, & Bernard, 2013). In addition, students are expected to benefit from peer mentoring in these communities, as discussed later in this chapter.…”
Section: Program Form and Structurementioning
confidence: 99%
“…Recent studies that have explored the impact on student GPA and retention are Winnie (2012), Berry (2014), Vaughan et al (2014), and Newman (2016). Some other studies (Williford et al, 2001;Lang, 2007;Cambridge-Williams et al, 2013;Miller and Lesik, 2014) have found that seminar participation increased student retention and graduation rates. Overall, therefore, most research has reported a positive impact on student performance and retention from first-year seminars.…”
Section: General Attitudes Toward Higher Educationmentioning
confidence: 91%
“…For some universities, FYS courses were most effective in either improving 4-year graduation rates (McGrath & Burd, 2012;Miller & Lesik, 2014;Schnell, Louis & Doetkott, 2003) or enhancing degree attainment within 5-years (Cambridge-Williams, Winsler, Kitsantas & Bernard, 2013;McGrath & Burd, 2012;Noble, Flynn, Lee & Hilton, 2007, Schnell, Louis & Doetkott, 2003. For other institutions, however, positive course effects were recorded for 4, 5, and 6-year graduation rates simultaneously (Lang, 2007;Starke, Harth, & Sirianni, 2001;Tuckman & Kennedy, 2011;Williford, Chapman, & Kahrig, 2001).…”
Section: Metric 2: Four Year Ftic Graduation Ratementioning
confidence: 99%